THE PARTITION DIMENSION OF ROSE GRAPHS AND ITS BARBELL - Dina Eka Nurvazly; Martha Magdalena Sihombing; Asmiati; Notiragayu (Departemen Matematika dan Sains Data FMIPA Universitas Andalas Padang, 2026)
The rose graph, denoted by R(C_n), n>=3 constructed by a cycle graph C_n with n isolated vertices that connect every two vertices in the cycle graph with one isolated vertex. The rose barbell graph, denoted by B_R(C_n) is a simple graph formed by connecting two rose graphs R(C_n) by edges v_1,v^'_1 as a bridge. In this paper, we determined the partition dimension of the rose graph and its barbell